INFLUENCE OF CASHBACK PROMOTION, E-SERVICE QUALITY, CUSTOMER SATISFACTION ON RE-USE INTEREST - Ahmad Munawar, Niknik; M. Rizky Mahaputra (Dinasti International Journal of Management Science, 2022)
Previous research is important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the reuse interest model through customer satisfaction during the covid-19 pandemic through the promotion of cashback and e-service quality. A Marketing Management Literature Study. The results of this research library are that: 1) cashback promotion has an effect on re-use interest; 2) e-service quality has an effect on interest in reuse; 3) customer satisfaction has an effect on interest in reuse.